2022
DOI: 10.3390/ph15121485
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Inhibitors for Therapeutic Management of Kidney Fibrosis

Abstract: Kidney fibrosis is a common pathophysiological mechanism of chronic kidney disease (CKD) progression caused by several underlying kidney diseases. Among various contributors to kidney fibrosis, transforming growth factor-β1 (TGF-β1) is the major factor driving fibrosis. TGF-β1 exerts its profibrotic attributes via the activation of canonical and non-canonical signaling pathways, which induce proliferation and activation of myofibroblasts and subsequent accumulation of extracellular matrix. Over the past few de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 153 publications
0
8
0
Order By: Relevance
“…It includes several strategies including Smad agonists/inhibitors and neutralizing antibodies against receptors/cytokines. However, the pleotropic nature of this pathway has limited their application due to potential side effects [176].…”
Section: Hypoxia As a Therapeutic Target In Ckdmentioning
confidence: 99%
“…It includes several strategies including Smad agonists/inhibitors and neutralizing antibodies against receptors/cytokines. However, the pleotropic nature of this pathway has limited their application due to potential side effects [176].…”
Section: Hypoxia As a Therapeutic Target In Ckdmentioning
confidence: 99%
“…Although PFD has been widely used to reduce pulmonary fibrosis [21], its effects remain largely unexplored in the renal field. Previous studies reported that PFD is a renoprotective agent that exerts its functions partly by inhibiting the TGF-beta signaling pathway [22,23]. Some studies also suggested that pirfenidone is a promising therapeutic agent for individuals with diabetic nephropathy [24].…”
Section: Discussionmentioning
confidence: 99%
“…Readers are referred to recent reviews and reports on the therapeutic targeting of TGF-β in renal, pulmonary, liver, and cardiac fibrosis [ 4 , 370 , 371 , 372 , 373 ] for further information about the role of TGF-β in fibrosis.…”
Section: Role Of Tgf-βs In the Pathophysiology Of Fibrosismentioning
confidence: 99%